Phenotypic Changes in T and NK Cells Induced by Sputnik V Vaccination - Anna A. Boyko; Maria O. Ustiuzhanina; Julia D. Vavilova; Maria A. Streltsova; Sofya A. Kust; Andrei E. Siniavin; Irina V. Astrakhantseva; Marina S. Drutskaya; Elena I. Kovalenko (Vaccines, 2023)
A highly effective humoral immune response induced by the Sputnik V vaccine was demonstrated in independent studies, as well as in large-scale post-vaccination follow-up studies. However, the shifts in the cell-mediated immunity induced by Sputnik V vaccination are still under investigation. This study was aimed at estimating the impact of Sputnik V on activating and inhibitory receptors, activation and proliferative senescence markers in NK and T lymphocytes. The effects of Sputnik V were evaluated by the comparison of PBMC samples prior to vaccination, and then three days and three weeks following the second (boost) dose. The prime-boost format of Sputnik V vaccination induced a contraction in the T cell fraction of senescent CD57+ cells and a decrease in HLA-DR-expressing T cells. The proportion of NKG2A+ T cells was down-regulated after vaccination, whereas the PD-1 level was not affected significantly. A temporal increase in activation levels of NK cells and NKT-like cells was recorded, dependent on whether the individuals had COVID-19 prior to vaccination. A short-term elevation of the activating NKG2D and CD16 was observed in NK cells. Overall, the findings of the study are in favor of the Sputnik V vaccine not provoking a dramatic phenotypic rearrangement in T and NK cells, although it induces their slight temporal non-specific activation.